I Go by The Name: The Naming of Indonesian Pop Singers’ Stage Names in Perspectives of Charactonym - Marsha Khairani Awanda Nugroho; Annisa Fitriana; Fariha Najda Fiaunillah; Changmia Anggraeni; Muhammad Haichal Alifiyanto (JL3T (Journal of Linguistics, Literature and Language Teaching), 2025)
Stage name is a popular phenomenon in the world of celebrities, especially singers. Through stage names, it is expected that the singers are more recognizable to the public. We argue that stage names might function as a charactonym in which the singers play a different character than they are in the real world. To prove this claim, we first attempted to reveal the types of stage names and second to unveil how the stage names function as charactonym. A collection of singers' stage names was investigated by employing the theories from Lyons (1977) theory that discusses the types of names, and Coates (2018) theory discusses names that form charactonyms. In this research, Indonesian singers such as Jaz are included in the type of name senses and the form of interpretation charactonym, while Budi Doremi is included in the type of name references and Hindia is included in the type of name denotation, both of which have the form of charactonym role playing. This research has the theoretical implication that looking at stage names in terms of charactonyms can be used as a guideline to investigate stage names from the perspective of charactonym.